The effects of macroeconomic, fiscal and monetary policy announcements on sovereign bond spreads - Afonso, António (2022)
We assess the impact of announcements corresponding to different fiscal and monetary policy mea-sures on 10-year sovereign bond yield spreads (relative to Germany) of 10 EMU countries during theperiod 01:1999-07:2016. Implementing country-fixed effects OLS regressions, we find that the Euro-pean Commission’s (EC) releases of the excessive deficit procedure significantly affect yield spreads. TheEC releases of higher debt and better budget balance forecasts contribute to the rise and the decline ofspreads, respectively. Moreover, we find that the announcements of the ECB’s key interest rates togetherwith the longer-term refinancing operations (LTROs) and the first covered bond purchase programme(CBPP1) negatively affect sovereign yield spreads in our sample of EMU countries. There was also somecapital market mispricing of the sovereign bond risk in the Euro area before the Global Financial Crisis,notably regarding government debt forecasts.